2007
DOI: 10.1093/nar/gkm024
|View full text |Cite
|
Sign up to set email alerts
|

Specificity, duplex degradation and subcellular localization of antagomirs

Abstract: MicroRNAs (miRNAs) are an abundant class of 20–23-nt long regulators of gene expression. The study of miRNA function in mice and potential therapeutic approaches largely depend on modified oligonucleotides. We recently demonstrated silencing miRNA function in mice using chemically modified and cholesterol-conjugated RNAs termed ‘antagomirs’. Here, we further characterize the properties and function of antagomirs in mice. We demonstrate that antagomirs harbor optimized phosphorothioate modifications, require >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
363
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(378 citation statements)
references
References 18 publications
15
363
0
Order By: Relevance
“…The next advance in AMO technology came from Krützfeldt et al 21,22 who employed 2¢OMe oligonucleotides with several PS bonds between the internucleotide linkages at each end of the molecule to defend against exonuclease attack (Table 1). A cholesterol group was attached to the 3¢-end to assist with delivery in vivo; this specific design of AMO was called an 'antagomir' .…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…The next advance in AMO technology came from Krützfeldt et al 21,22 who employed 2¢OMe oligonucleotides with several PS bonds between the internucleotide linkages at each end of the molecule to defend against exonuclease attack (Table 1). A cholesterol group was attached to the 3¢-end to assist with delivery in vivo; this specific design of AMO was called an 'antagomir' .…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…Although the traditional drug targets have been protein products, the recent development of microRNA derivatives with increased stability and binding efficiency, such as AMOs (antimicroRNA oligonucleotides) and LNAs (locked nucleic acids) represent potentially important developments for such purpose. [36][37][38] For example, targeting an HRM that plays a survival role in hypoxia could provide a new angle in targeting a notoriously refractory fraction of tumor cells. Moreover, manipulation of select microRNAs could synergize with conventional therapies.…”
Section: Towards Future Applications In Clinical Oncologymentioning
confidence: 99%
“…To strengthen our hypothesis, we administered locked nucleic acidanti-miR29b injection in vivo to conclusively show miR29b regulation in BBB permeability. We administered scramble miR and anti-miR29b into CBS þ / À mice through intracerebral route, as explained by Krutzfeldt et al 40 The author described that local administration of antagomiR-16 is effective as compared with systemic infusions, most likely because of inability of oligonucleotides to cross the blood-brain barrier. 40 As compared to CBS þ / À þ scramble miR mice, CBS þ / À þ anti-miR29b mice showed significant decrease in miR29b levels along with considerable decrease in FITC-BSA leakage through brain pial venules (Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…We administered scramble miR and anti-miR29b into CBS þ / À mice through intracerebral route, as explained by Krutzfeldt et al 40 The author described that local administration of antagomiR-16 is effective as compared with systemic infusions, most likely because of inability of oligonucleotides to cross the blood-brain barrier. 40 As compared to CBS þ / À þ scramble miR mice, CBS þ / À þ anti-miR29b mice showed significant decrease in miR29b levels along with considerable decrease in FITC-BSA leakage through brain pial venules (Supplementary Figure 2). In agreement to our finding, Zhou et al 41 also found miR29 family member 'miR29a' involvement in the regulation of intestinal membrane permeability in patients with irritable bowel disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation